MODEL LEMBAGA KEUANGAN MIKRO SYARIAH DI PONDOK PESANTREN : Studi Kasus Kopotren Riyadhul Muta'alimin - Djajuli, Akhmad (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2021)
ABSTRACT This study aims to find out the LKMS Model at Riyadhul Muta'alimin Islamic Boarding School in Bogor. The research method used is a qualitative descriptive approach. Data collection techniques were obtained from interviews, observation and documentation studies. While the data analysis techniques used are Miles and Huberman. The results showed that the Riyadhul Muta'alimin Kopontren had a considerable influence on the economy in Riyadhul Muta'alimin Islamic Boarding School because the Islamic boarding school's finances were almost entirely managed or were the responsibility of the Kopontren so there was a need for a special model to be implemented by Kopontren to manage Kopontren. again. Keywords: Islamic Boarding Schools, LKMS, LKMS Model in Islamic Boarding Schools.